Case Report: Autoimmune hemolytic anemia associated with ovarian teratoma in a 13-year-old: a rare paraneoplastic presentation - Althobaiti, Salman; Assinnari, Ahmad; Alharbi, Mayes; Kurdi, Razan (Frontiers in Pediatrics, 2025)
BackgroundAutoimmune hemolytic anemia (AIHA) is a rare and potentially life-threatening condition in the pediatric population. While often associated with autoimmune or lymphoproliferative disorders, its occurrence in conjunction with benign ovarian tumors, such as mature cystic teratomas, is exceptionally rare.Case presentationA 13-year-old previously healthy female presented with a one-week history of progressive pallor, jaundice, and fatigue. Initial laboratory tests revealed severe anemia (Hb 5.6 g/dL), elevated LDH, indirect hyperbilirubinemia, undetectable haptoglobin, and a positive direct antiglobulin test (DAT) for IgG, confirming warm AIHA. Imaging studies, including pelvic ultrasound and MRI, identified a large complex cystic ovarian mass, consistent with a mature cystic teratoma. The patient underwent exploratory laparotomy with right salpingo-oophorectomy without requiring blood transfusions. Postoperatively, there was complete resolution of hemolysis, normalization of laboratory values, and no recurrence over a 2-month follow-up period.ConclusionThis case highlights a diagnostic challenge and underscores the importance of recognizing paraneoplastic AIHA in children, even in the context of benign tumors. It also supports a potential autoimmune–tumor association, emphasizing the value of timely diagnosis and surgical intervention.